Distinct Immunophenotypes of T Cells in Bronchoalveolar Lavage Fluid From Leukemia Patients With Immune Checkpoint Inhibitors-Related Pulmonary Complications - Kim, Sang T.; Sheshadri, Ajay; Shannon, Vickie; Kontoyiannis, Dimitrios P.; Kantarjian, Hagop; Garcia-Manero, Guillermo; Ravandi, Farhad; Im, Jin S.; Boddu, Prajwal; Bashoura, Lara; Balachandran, Diwakar D.; Evans, Scott E.; et al. (Frontiers in Immunology, 2021)
Patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) treated with immune checkpoint inhibitors (ICIs) are at risk of pneumonitis as well as pneumonia (combined henceforth as ICI-related pulmonary complications). Little is known about the cellular and molecular mechanisms underlying ICI-related pulmonary complications. We characterized lymphocytes from bronchoalveolar lavage (BAL) fluid and peripheral blood from seven AML/MDS patients with pulmonary symptoms after ICI-based therapy (ICI group) and four ICI-naïve AML/MDS patients with extracellular bacterial or fungal pneumonias (controls). BAL T cells in the ICI group were clonally expanded, and BAL IFNγ+ IL-17- CD8+ T and CXCR3+ CCR6+ Th17/Th1 cells were enriched in the ICI group. Our data suggest that these cells may play a critical role in the pathophysiology of ICI-related pulmonary complications. Understanding of these cell populations may also provide predictive and diagnostic biomarkers of ICI-related pulmonary complications, eventually enabling differentiation of pneumonitis from pneumonia in AML/MDS patients receiving ICI-based therapies.